Comparative Analysis of MicroRNA Expression among Benign and Malignant Tongue Tissue and Plasma of Patients with Tongue Cancer - Rabinowits, Guilherme; Bowden, Michaela; Flores, Ludmila M.; Verselis, Sigitas; Vergara, Victoria; Jo, Vickie Y.; Chau, Nicole; Lorch, Jochen; Hammerman, Peter S.; Thomas, Tom; Goguen, Laura A.; Annino, Donald; et al. (Frontiers in Oncology, 2017)
Background: Identification of a miRNA pattern to be used as a biomarker for HNSCC is challenging given the heterogeneity of the disease and different methodologies used. To better define the field, we performed a prospective analysis of blood, tumor and paired benign tissues in tongue SCC patients. Methods: Plasma samples were collected prior to surgery and paired tumor and benign tissue blocks were collected from tongue cancer resections. Circulating free and exosomal-miRNA, and paired tumor and benign tissues-miRNA were analyzed. TaqMan-based miRNA arrays were used to quantitate the expression of 747 human miRNAs. The comparative Ct method assessed the miRNA profile results, and student t-test determined statistical significance between tumor and benign samples. Results: Sixteen of 359 miRNAs detected were differentially expressed between paired tumor and benign tissue. Nine were upregulated and 7 downregulated in tumor tissue. All 9 upregulated, and 6 of 7 downregulated tumor-miRNAs were expressed in circulating exosomes. In contrast, 8 of 9 upregulated and 4 of 7 downregulated tumor-miRNAs were circulating free in the plasma. Conclusions: An aberrantly expressed pattern of miRNA was identified in both tumor and plasma of patients with tongue SCC, suggesting this may be a biomarker for SCC of the oral tongue. Circulating exosomes appear to be a more reliable method for evaluation of circulating tumor-miRNA expression. Further studies with a larger cohort of patients and serial blood samples are needed to validate our findings.